Filogenia molecular e taxonomia de Coprophanaeus (Megaphanaeus) d'Olsoufieff, 1924 (Coleoptera : Scarabaeidae) - Maldaner, Maria Eduarda (2017)
The genus Coprophanaeus d'Olsoufieff, 1924 is characterized by having the clypeus with three indentations forming two acute teeth and the anterior tibia quadridentate. Comprising around 40 valid species, Coprophanaeus has been considered a monophyletic group with three subgenera: Coprophanaeus sensu stricto, Metallophanaeus, and Megaphanaeus. Megaphanaeus is diagnosed by a row of short setae on the posterior surface of the protibia and uneven interstriae of elytra. The subgenus has four valid species: C. (Megaphanaeus) lancifer (Linné, 1767), C. (Megaphanaeus) ensifer (Germar, 1821), C. (Megaphanaeus) bonariensis (Gory, 1844) and C. (Megaphanaeus) bellicosus (Olivier, 1789). Megaphanaeus species are distributed along most of eastern South America - on the Amazonian Rain Forest (C. lancifer), Atlantic Rain Forest (C. bellicosus), Brazilian Cerrado (C. ensifer), and Chaco (C. bonariensis). Regarding these species, no phylogenetic relationship hypotheses have been proposed so far and authors disagree about the placement of C. bellicosus, whether it belongs to Coprophanaeus sensu stricto or Megaphanaeus. Also, based on previous analysis of pinned specimens, C. ensifer shows variation in size and color in agreement to different habitats, but the morphological structure remains the same. Thus, our aims were (I) to test if Megaphanaeus is a monophyletic group, (II) verify to which subgenus C. bellicosus belongs, (II) to test if C. ensifer is a complex of species and (IV) promote nomenclatural stability of taxa at specific level in Megaphanaeus. 158 specimens were collected and three mitochondrial and one nuclear marker were sequenced: COI (681bp), COI-II (1324bp), 16S (532bp) e 28S (982bp). Sequences with good quality were concatenated in two matrices: one with fourteen terminals and ten species (C. lancifer, C. bonariensis, C. ensifer, C. bellicosus, C. saphirinus, C. spitzi, Sulcophanaeus faunus, Phanaeus sororibispinus, Oxysternon conspicillatum e Diabroctis mirabilis) and the other with 27 terminals and fifteen species (in addition to those mentioned above, C. machadoi, C. dardanus, C. telamon, C. cyanescens and O. macleayi were included). Both matrices were analysed under three methods of phylogenetic inference: Maximum Parsimony (MP), Maximum Likelihood (ML), and Bayesian Inference (BI). For genetic diversity of C. ensifer a matrix with 67 sequences of COI were submitted to analysis of genetic distance, haplotypic diversity and molecular variance. Megaphanaeus is here considered as monophyletic including C. bellicosus as sister-group to (C. bonariensis (C. lancifer, C. ensifer)). C. spitzi and C. cyanescens are shown as sister-group of all Megaphanaeus on analysis with two markers, but analyzing four markers, the sistergroup of Megaphanaeus is C. saphirinus. 34 haplotypes were found in the population analysis of C. ensifer, only ten were shared by two individuals or more. The group analysis between of C. ensifer yielded in non significative results of differentiation, thus there is no evidence for cryptic or new species in this group using COI sequences. To promote nomenclatural stability to names related to Megaphanaeus, a neotype of Scarabaeus lancifer Linné, 1767 was designated as well as a lectotype to Phanaeus septentrionalis Pêssoa, 1934 and to Copris ensifer Germar (1821).